Determination of epristeride by its quenching effect on the fluorescence of L-tryptophan - Ai-Qin Gong; Xia-Shi Zhu (Elsevier, 2013)
A rapid, novel spectrofluorimetric method to determine epristeride (EP) in biological fluids and a pharmaceutical formulation was developed, based on the fact that fluorescence intensity of l-tryptophan could be quenched by EP in the medium of pH=9.0. The various factors influencing fluorescence quenching were discussed. The quenching mechanism was investigated with the quenching type, synchronous fluorescence spectra and quantum efficiency. Under the optimized conditions, fluorescence quenching value (ÎF=Fl-tryptophanâFEPâl-tryptophan) showed a good linear relationship with the EP concentration ranging from 0.4 to 12.0Â Î¼g/mL. The linearity, recovery and limit of detection demonstrated that the proposed method was suitable for EP determination in biological fluids and EP tablets. The method was successfully applied to the analysis of EP in real samples and the obtained results were in good agreement with the results of the official method. Keywords: Epristeride, l-tryptophan, Fluorescence quenching method